Accidental pregnancy in Cooper-T 380A intrauterine device users - Rojas, Elizabeth (2015)
Objectives: To evaluate the evolution of accidental pregnancies that occur in users of intrauterine device (IUD) Copper T 380A. Design: Retrospective, descriptive study. Location: Family Planning Office of the Archbishop Loayza Hospital. Material and Methods: We reviewed the medical records of patients accidentally pregnant after being studied IUD users. Results: Occurred 46 accidental pregnancies in the study period, of which 7 will not be able to obtain information about termination of pregnancy. Of all the patients studied 59% were to term and 41% ended in abortion, 15.4% and 25.6% induced spontaneous. Only one case of abortion endometritis (2.6%) was recorded. Conclusions: accidental pregnancies T380A IUD users, 59% resulted in labor at term and 41% in abortion.